Economic Empowerment Of Santripreneur-Based Islamic Boarding Schools At Nurul Amanah Islamic Boarding School, Bangkalan - Anisa Putri Armita; Luluk Hanifah (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2023)
Islamic boarding schools have the responsibility to develop the potential of students and empower them in all fields including economic aspects. This is what has spurred a number of Islamic boarding schools to try to combine the religious education system with entrepreneurial training. With the aim of supporting the main task of Islamic boarding schools, namely providing religious knowledge. So that Islamic boarding schools are not only producing a spiritually competent generation, but also producing an economically competent generation. The research conducted at the Nurul Amanah Bangkalan Islamic Boarding School used qualitative research methods. The data collection techniques used in this research included documentation, observation and in-depth interviews with students and caregivers at the Nurul Amanah Bangkalan Islamic Boarding School. Nurul Amanah Islamic Boarding School is an Islamic boarding school that implements a santripreneur program for students to become entrepreneurs so that they can empower the Islamic boarding school's economy. Therefore, this research aims to determine the economic empowerment of santripreneur-based Islamic boarding schools at the Nurul Amanah Bangkalan Islamic Boarding School.